Prevalence, patterns and factors associated with injury: comparison between elite Malaysian able-bodied and para-badminton players - Muhammad Noh Zulfikri Mohd Jamali, M. N. Z. M.; Selvanayagam, V. S.; Hamid, M. S. A.; Yusof, A. (The Physician and Sportsmedicine, 2022)
Objectives